2016
DOI: 10.3319/tao.2015.11.30.01(oc)
|View full text |Cite
|
Sign up to set email alerts
|

The Evident Role of Clouds on Phytoplankton Abundance in Antarctic Coastal Polynyas

Abstract: High-level primary production (PP) sustainability in the Antarctic coastal polynyas has not been adequately addressed. We investigated the relationship between the Antarctic coastal polynyas phytoplankton biomass (as reflected by Chl-a) and the cloud cover, which dominantly influences the light conditions. Phytoplankton biomass in Antarctic coastal polynyas showed a robust correlation with the photosynthetically active radiation (PAR) and the cloud fraction. However, a different relationship was observed betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 38 publications
0
3
1
Order By: Relevance
“…However, no pronounced relationships were observed among these variables with Chl-a in the Bransfield Strait. In contrast to La and Park (2016) who presented robust correlations between cloud cover, cloud height, or PAR with Chl-a in the Antarctic coastal polynyas, the weak correlations in the present study implied that light condition is not a key limiting factor for chlorophyll in the Bransfield Strait. Note that the response of Chl-a to the high cloud fraction was opposite to the middle and low cloud fractions, albeit their moderate to weak correlations (supplementary Figs.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…However, no pronounced relationships were observed among these variables with Chl-a in the Bransfield Strait. In contrast to La and Park (2016) who presented robust correlations between cloud cover, cloud height, or PAR with Chl-a in the Antarctic coastal polynyas, the weak correlations in the present study implied that light condition is not a key limiting factor for chlorophyll in the Bransfield Strait. Note that the response of Chl-a to the high cloud fraction was opposite to the middle and low cloud fractions, albeit their moderate to weak correlations (supplementary Figs.…”
Section: Resultscontrasting
confidence: 99%
“…Spatial and temporal variation of phytoplankton distribution has often compared with complex water column structures (Basterretxea and Arístegui 1999). Additionally, a recent study suggested cloud cover influences phytoplankton biomass in the Southern Ocean (La and Park 2016). Longterm variation in phytoplankton biomass could be driven by climate change, such as the Southern Annular Mode (SAM) and El Niño Southern Oscillation (ENSO), since plankton ecosystems are associated with sea ice change and water column stability Venables et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…L'Ecuyer et al (2015) relied on multiple variables from MERRA in their assessment of the state of the global energy budget in the early twenty-first century, while Trenberth et al (2015) used it to examine top-ofatmosphere (TOA) radiative fluxes and surface temperature in the context of climate variability. Applications of MERRA data for polar studies include the work of La and Park (2016) on the effect of clouds on phytoplankton in Antarctica, as well as a paper by Letterly et al (2016) concerning the impact of winter clouds on summer sea ice in the Arctic. Hundreds of other papers relying on MERRA data are in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Rainfall can also affect gonad development in birds. This depends on the light intensity (Dawson 2015 ), which during rainfall (when the sky is overcast) is less than on sunny days (Mumby et al 2001 ; La and Park 2016 ) and the gonads then develop more slowly. In consequence, the birds' breeding season is delayed.…”
Section: Discussionmentioning
confidence: 99%